The Impact of Social Media Usage on Mental Health Among College Students: Patterns, Psychological Effects, and Implications for Well-being - Shrestha, Manju; Adhikari, Subash (International Journal of Atharva, 2024)
This study explores the impact of social media usage on the mental health of college students, focusing on usage patterns and psychological effects. A descriptive research design was employed, with a sample size of 121 respondents selected through stratified random sampling. Data was gathered using a closed-ended questionnaire featuring a 5-point Likert scale. The findings reveal that social media consumption varies significantly among students, with a majority experiencing mood changes and potential addiction. Furthermore, the analysis highlights the influence of social media on daily activities, sleep patterns, and overall mental well-being. The study provides valuable insights into the relationship between social media usage and mental health, offering a foundation for future research on mitigating negative psychological impacts among students.